PENGARUH PENGGUNAAN METODE BERVARIASI TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Khairani, Farida; Nurzannah, Nurzannah; Rudi Setiawan, Hasrian (CV. Lafadz Jaya, 2025)
This study aims to examine the effects of lecture method, Contextual Teaching and Learning (CTL), and discussion method on students’ learning interest and learning outcomes in Islamic Religious Education at SMP Hidayatul Islam Yahdi, Helvetia, Deli Serdang Regency, North Sumatra, academic year 2024/2025. The research employed a quantitative approach with a quasi-experimental design using a control group pre-test-post-test. Data were collected through questionnaires and tests, then analyzed by Structural Equation Modeling using Partial Least Square (PLS) software. The results indicate that the lecture method significantly affects learning interest (p = 0.049) and learning outcomes (p = 0.010). The CTL method also significantly influences learning interest (p = 0.008) and learning outcomes (p = 0.012). The discussion method has a significant effect on learning interest (p = 0.000) and learning outcomes (p = 0.002). Overall, the combined influence of these three methods on students’ learning interest is 77.2%, while their influence on learning outcomes is 81.8%. This study highlights the importance of varied teaching methods in improving both interest and learning achievement in Islamic Religious Education.